“Double Whammy” - a case of nephrotic syndrome on rituximab infusion with extensive herpes zoster: a case report of an 8-year-old female child - Nilakhawala, Shamiyaz D.; Rai, Rajesh; Inamdar, Prithi; Nalikha, Ravi P. (International Journal of Contemporary Pediatrics, 2025)
This paper presents the case of an 8-year-old female patient, diagnosed with steroid-resistant nephrotic syndrome (SRNS), who developed herpes zoster while on Rituximab treatment. The patient presented with a vesicular rash, fever, and headache. She was started on intravenous acyclovir and managed with symptomatic treatment. The patient responded well to the treatment, with resolution of symptoms and was discharged with guidance on hygiene practices. This case highlights the potential for herpes zoster infection in immunosuppressed patients, particularly those with SRNS receiving Rituximab, and the importance of early diagnosis and antiviral treatment to prevent complications.